(untitled) (The Pakistan Development Review, 2003)
The focus of this write-up is on three points. First: development is a multidimensional process involving major changes not only in socio-economic structures and institutions but also in popular attitudes and perceptions. Second: these changes, however anti-status quo, can be initiated, maintained, and speeded up if some powerful motivational factor comes into operation, as happened during the revolutionary Pakistan Movement. Third: the countrywide enthusiastic celebration of the year 2003 as Madar-e-Millat Year has proved to be one such motivational factor as it has brought about an unusual awakenance among Pakistan’s womenfolk to demand a rightful place in all walks of life. This is heartening especially because nearly half of the country’s population has terribly lagged behind in every conceivable sphere of development. This newly acquired awakenance can be and should be mobilised for speeding up the process of development by strengthening women’s participatory role in all political, economic, cultural, and even religious activities.